VARIATIONS OF RED COLOR COVERAGE OF CULTURED NEON TETRA (Paracheirodon innesi) FOR BREEDING IMPROVEMENT STRATEGIES - Ruby Vidia Kusumah; Dinar Tri Soelistyowati; Alimuddin Alimuddin; Melta Rini Fahmi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2021)
Red color coverage (RCC) is a commercial trait developed and refined to improve the appearance of many ornamental fish commodities. In neon tetra, the status of variation of RCC is not yet investigated or reported. This study aimed to analyze the RCC variation of cultured neon tetra as a basis for breeding strategies. A total of 900 neon tetras (standard length, SL, of 2.29 ± 0.16 cm) were collected from Bojongsari, Curug, and Pondok Petir fish farms located in Depok Districts, West Java. All fish were relocated and reared in a fish farm specialized in culturing neon tetra for two weeks using nine aquariums with photoperiod set up of 12 hours bright and 12 hours dark. The RCC traits were determined according to the percentages of RCC length (%LRCC), RCC width (%WRCC), and RCC area (%ARCC) and quantified using the digital image method. The result showed that the RCC varied by sex, size, and original location (P<0.05) in a low coefficient of variation (1.89%-11.41%). The RCC values in the male group were higher than that of females based on %LRCC and %ARCC parameters (P<0.05). Males had the highest %LRCC at size LXL, which was correlated with SL (r 0.25, P<0.1), of females at M size. The %LRCC values of the neon tetra population from the Bojongsari farm were higher than those from the other locations. Based on these findings, breeding strategies of the RCC traits should consider sex, size, and population (farm location) variations. Specifically for neon tetra, this strategy should be based on selecting the SL or %LRCC parameter of M for females and LXL for males.